2006
DOI: 10.1063/1.2392720
|View full text |Cite
|
Sign up to set email alerts
|

Rewritable photonic circuits

Abstract: The authors present a technique that allows to modify the local characteristics of two-dimensional photonic crystals by controlled microinfiltration of liquids. They demonstrate experimentally that by addressing and infiltrating each pore with a simple liquid, e.g., water, it is possible to write pixel by pixel optical devices of any geometry and shape. Calculations confirm that the obtained structures indeed constitute the desired resonators and waveguide structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(65 citation statements)
references
References 25 publications
0
65
0
Order By: Relevance
“…Such a structure can be used as a sensor, whose principle of operation is based on the cut-o wavelength shift caused by the in ltration of the holes. In ltration can be performed by various selective in ltration techniques, which have been experimentally demonstrated, such as using an integrated micro uidic circuit [24], an actuated microtip [25] or micropipette [26] with a high precision and good reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Such a structure can be used as a sensor, whose principle of operation is based on the cut-o wavelength shift caused by the in ltration of the holes. In ltration can be performed by various selective in ltration techniques, which have been experimentally demonstrated, such as using an integrated micro uidic circuit [24], an actuated microtip [25] or micropipette [26] with a high precision and good reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, postprocessing tuning techniques able to compensate for fabrication imperfections are particularly demanded. Various postprocessing tuning techniques have been demonstrated, such as differential thermal tuning, 7,8 wet chemical digital etching, 9 atomic layer deposition, 10 atomic force microscope nano-oxidation, 11 liquid crystal infiltration, 12 and photodarkening of a chalcogenide glass placed on top of the microcavity. 13 Most of these techniques either modify the properties of the whole sample, which prevents the local tuning of a single nanocavity, or need extra materials and processing tools.…”
mentioning
confidence: 99%
“…8 However, the nanometer-scale precision required to realize sophisticated and optimized geometries eventually becomes a limiting factor in achieving high-Q cavities, as pointed out by Asano et al 9 Recently, several groups have reported demonstrations of postprocessed PCS structures, granting them the flexibility to tune or reconfigure device properties to suit various applications at any time after the PCS is fabricated. [10][11][12][13] In particular, Intonti et al introduced a "pixel by pixel" approach for writing and rewriting PCS defect structures via fluid infiltration. 12 Theoretical results of Tomljenovic-Hanic et al showed that high Q-factor cavities could be achieved in PCSs from fluid infiltration 14 by forming doubleheterostructured geometries, providing an integrated optofluidic sensing architecture.…”
mentioning
confidence: 99%
“…[10][11][12][13] In particular, Intonti et al introduced a "pixel by pixel" approach for writing and rewriting PCS defect structures via fluid infiltration. 12 Theoretical results of Tomljenovic-Hanic et al showed that high Q-factor cavities could be achieved in PCSs from fluid infiltration 14 by forming doubleheterostructured geometries, providing an integrated optofluidic sensing architecture.…”
mentioning
confidence: 99%